Implementasi Dasar-dasar Teologi, Filosofi, Psikologi dan Sosiologi untuk Mewujudkan Kualitas Pendidikan di Indonesia - Dariyo, Agoes (LPPM IAINU Kebumen, 2023)
The quality of education in Indonesia is relatively low, when compared to other countries in the world, namely the quality of education in Indonesia is ranked number 72 out of 79 countries in the world. As a result, Indonesia has not been able to face global competition. Based on this idea, the purpose of this research is to find out how the implementation of the theology, philosophy, psychology and sociology foundations is used to realize the quality of education in Indonesia. This study uses a qualitative-descriptive approach with data collection techniques through literature review such as: government policy regulations, legislation, books, journals, or relevant literature. Data analysis used a thematic approach, namely analyzing data based on research themes. The results of the research show that education is a process of activity for the development of all potentials in order to improve human life. Educational activities are based on a legal basis (1945 Constitution, Pancasila, Law No. 20 of 2003 concerning the National Education System). Educational activities are carried out with reference to the national curriculum. In addition, education also pays attention to the 8 national education standards. The implementation of education must involve 4 main foundations, namely theology, philosophy, psychology and sociology in order to realize the quality of education in Indonesia.